2018
DOI: 10.21608/bjas.2018.191068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Rotavirus Genotypes Infection in Egypt

Abstract: Rotavirus have been reported as the principal causal pathogen of acute gastroenteritis and one of the leading causes of child morbidity and mortality in Egypt .This study aimed to investigate biological , serological and molecular Rotavirus genotypes infection in Egypt . The blood and stool clinical specimens were collected randomly from 100 patients .They were analyzed for the presence of antigen and the antibody using enzyme-linked immunosorbent assay (ELISA). Rotavirus antigen in stool and antibodies in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…P [8], P [4], and P[6] genotypes P [8], P [4], and P [6] are the major P genotypes, accounting for nearly 99% of all human RV infections occurring in Egypt. P [8] was the most prevalent genotype in 2002 and between 2009 and the present studies reported that P [8] represented >50% of all P genotypes detected in many regions of Egypt during the study period [56,62,64,65,67,[69][70][71]; P [4] and P [6] were the second and third most common P genotypes identified, respectively [56,61,64,[66][67][68][69]. Other investigations reported that the P [4]…”
Section: G1-g4 Genotypessupporting
confidence: 58%
See 2 more Smart Citations
“…P [8], P [4], and P[6] genotypes P [8], P [4], and P [6] are the major P genotypes, accounting for nearly 99% of all human RV infections occurring in Egypt. P [8] was the most prevalent genotype in 2002 and between 2009 and the present studies reported that P [8] represented >50% of all P genotypes detected in many regions of Egypt during the study period [56,62,64,65,67,[69][70][71]; P [4] and P [6] were the second and third most common P genotypes identified, respectively [56,61,64,[66][67][68][69]. Other investigations reported that the P [4]…”
Section: G1-g4 Genotypessupporting
confidence: 58%
“…Each genotype was predominant over a specific time period. The first study genotyping human RV, which was conducted in Egypt in 1992, revealed that G1 and G4 were equally predominant genotypes [53]; however, other reports have revealed that the G1 genotype was mostly predominant in 2002 [56], between 2009 and 2012 [62][63][64], 2015-2017 [67,68], and 2018-2020 [69,70] G4 was the predominant strain during the 1992-1993 season [53] and in 2006 [60].…”
Section: G1-g4 Genotypesmentioning
confidence: 99%
See 1 more Smart Citation